2019
DOI: 10.12659/msm.915921
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Vacuum Sealing Drainage Treatment Combined with Skin Flap Transplantation and Antibiotic Bone Cement on Chronic Tibia Osteomyelitis: A Case Series Study

Abstract: Background Chronic osteomyelitis is one of the currently refractory diseases. The aim of this study is to discuss the method and curative effects of vacuum sealing drainage (VSD) treatment combined with skin flap transplantation and antibiotic bone cement for chronic tibia osteomyelitis. Material/Methods For this study, 18 cases of open fracture secondary chronic tibia osteomyelitis were selected. After the granulation tissue of the wound surface became fresh and infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Study characteristics of the eight high-quality studies, published between 2009 and 2019, are shown in Table 2 . Six cohort studies [ 31 36 ] and two case-control studies [ 30 , 37 ] were included in this systematic review. Four of the cohort studies had a prospective [ 31 , 34 36 ] and two a retrospective design [ 32 , 33 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study characteristics of the eight high-quality studies, published between 2009 and 2019, are shown in Table 2 . Six cohort studies [ 31 36 ] and two case-control studies [ 30 , 37 ] were included in this systematic review. Four of the cohort studies had a prospective [ 31 , 34 36 ] and two a retrospective design [ 32 , 33 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Six cohort studies [ 31 36 ] and two case-control studies [ 30 , 37 ] were included in this systematic review. Four of the cohort studies had a prospective [ 31 , 34 36 ] and two a retrospective design [ 32 , 33 ], respectively. NPWT duration varied and was often not reported.…”
Section: Resultsmentioning
confidence: 99%
“…Amputation is frequently utilised as a surrogate for poor outcome or treatment failure; however, there is an increasing body of literature supporting early amputation under circumstances, where the outcome is likely to be poor, or the morbidity of treatment high. Multiple studies in trauma have demonstrated that early amputation results in fewer overall complications, more rapid resolution of symptoms and equivalent or superior functional outcomes to those undergoing limb reconstruction techniques [44][45][46][47]. It is important, therefore, that the concept of functional amputation, where this approach is considered as a treatment choice rather than a last resort, is developed and discussed with patients at an early stage.…”
Section: Amputationmentioning
confidence: 99%
“…Liu et al (2016) studied the efficacy of NPWT and antibiotic-impregnated bone cement in the management of soft tissue defects and infection and found this combination could accelerate wound healing and decrease infection recurrence of soft tissue defects and infection compared with NPWT therapy only [12]. Li et al (2019) demonstrated that the combined use of NPWT and antibiotic-impregnated bone cement can be particularly effective and result in less complications for the management of chronic tibia osteomyelitis [13].…”
Section: Discussionmentioning
confidence: 99%